Inovasi Musikal Reyog Kawula Bantarangin di Desa Kauman Ponorogo Jawa Timur - Mahatma, Prasasti Resi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
The Kawula Bantarangin Reyog Ponorogo Group in Kauman Village, Kauman District, Ponorogo Regency, has made a new work outside the musical standard commonly used in Reyog Obyogan shows, which uses non-traditional musical instruments to create something new. Technically, there is a change in the garap that brings out different musical nuances into the show.This paper focuses its approach on musical-contextual events. The perspectives of Robert J. Sternberg, Utami Munandar, and Bernedeca Prihatini Dwi Riyani became a reference to the writer's perspective to describe the innovations of the Reyog Kawula Bantarangin group.The description of the form of musical innovation is guided by the perspective of Alan P. Merriam, Barnett, and Koentjaraningrat.This article also explains how innovation is formed from the dimensions of creativity in the work of Reyog's musical accompaniment which is driven not only by internal factors, but also by external factors, namely the existence of the Reyog Festival which motivates the Reyog Kawula Bantarangin actors to continue innovating. The form of work was originally based on Reyog Obyog, but then converted into an innovative work. It has an internal impacts, that it can grow confidence and stimulate a sense of creativity. As a result, the works of the Reyog Kawula Bantarangin group now receives wider recognition from the public, has increased stage performances, and increased financial income. There is also an external impact, that it has triggered a healthy competition of creativity with other Reyog groups. This way, in the end, the Reyog Ponorogo art will continue to develop and can be kept away from extinction.